Perlindungan Hak Debitur Pinjaman Online (Pinjol) Dalam Perspektif Cyber Law - Rizka Rahadiyani Aisyah; Nurul Bazroh; Zahwa Rizqi Laurina; Yosephine Fransisca; Nazzari Azka (Jurnal Hukum Statuta, 2022)
The development of technology that is not limited to the current digital era, is more complete with the presence of one form of application of information technology in the financial sector, namely the Online Loan application. Many people think that this Online Loan is an easy and fast solution to get money. The development of the fintech industry is also attached to the negative stigma of the community, especially in the way of billing. The issue of Online Loans or Financial Technology Peer To Peer Lending (Fintech P2P) is increasingly in the public spotlight. Various cases of violations of Fintech Companies began to appear in the mass media. There are various types of violations by Fintech Companies. Starting from intimidating billing (Article 368 of the Criminal Code and Article 29 in conjunction with 45 of the ITE Law), personal data dissemination (Article 32 in conjunction with Article 48 of the ITE Law), fraud (Article 378 of the Criminal Code). Unfortunately, the legal solution to this problem is still minimal, so similar cases keep popping up. This journal contains legal issues on illegal online loans and forms of solving online loan problems that are currently rampant. The purpose of this journal is to find out the resolution of security and safety threats carried out by creditors against debtors in their activities online loans are illegal at this point. This journal uses the research method of the ITE Law approach. The results of this journal are the existence of legality of online loan companies, the violation of the rights of online loan service users is expected to minimize the risk of violating user rights and if the violation of the rights of service users persists, the authorities can more easily reach the service provider because of the availability of documents. Complete information about the service provider.